Leadership alone is not enough: Why culture and satisfaction matter more in developing employee agility? - Suparjiman; Alfatah, Reza Fikri; Yuniarti, Yuti (University of Islam Malang, 2025)
Due to the intense rivalry in the communications industry, businesses require adaptive employees to keep staying resilient. While various factors have been examined to support employee agility, the combined roles of organizational culture transformation and leadership style in shaping employee satisfaction and agility remain underexplored, especially in the context of telecommunications sector. This study investigates how organizational culture transformation and leadership style influence employee satisfaction and, in turn, employee agility. A quantitative approach was employed by collecting data from 150 employees of one of the largest telecommunications firms in Indonesia, using simple random sampling. The data were analyzed using partial least squares structural equation modeling. The findings show that leadership style and culture transformation both significantly enhance employee satisfaction. Moreover, culture transformation directly strengthens employee agility, whereas leadership style does not have a direct effect on agility. Although previous studies suggest that leadership style can directly shape agility, this study demonstrates it does not, because employees require not only guidance and inspiration from their leaders but also a strong, supportive culture to feel safe, encouraged, and motivated to adapt and take initiative, which are key elements of agility.